Peran Media Infografis Dalam Meningkatkan Minat Belajar Siswa Bidang Studi Pai Di Sdn 02 Banjar Sari Labuhan Haji Lombok Timur - Nasri (MULTIPLE: Journal of Global and Multidisciplinary, 2024)
This research aims to analyze the role of infographic media in increasing students' interest in learning in the subject of Islamic Religious Education on the material "Ablution". Infographic media is considered a tool that has the potential to facilitate understanding of PAI concepts in a visual, attractive and easy to understand manner. The research method used is descriptive qualitative research. Data was collected by distributing questionnaires regarding students' interest in learning about PAI subjects before and after using infographic media. The results of the research showed a significant increase in understanding the concept of ablution, in addition, there was a positive increase in students' interest in learning about PAI subjects. These findings show that infographics have an important role in increasing students' interest in learning and are able to provide and facilitate understanding of PAI learning concepts.